PERANCANGAN SISTEM INFORMASI AKUNTANSI HARGA POKOK PRODUKSI PADA CV AULIA PRINTING - Fairuz, Nabila Nur; Oktarida, Anggeraini; Ardiani, Susi (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2023)
This final report aims to design an accounting information system for cost of goods manufacture using Micorosft Excel on orders from CV Aulia Printing In writing this final report, the object under study is the calculation of the cost of goods manufactured on orders for banners, brochures and invitations in the period January 2023. The data source that the authors took was primary data which included the results of the author's interview with the leadership of CV Aulia Printing. Data collection techniques used by the author are interviews and documentation. The author conducted an analysis of the accounting information system at CV Aulia Printing. The author knows that the company has made a report on the cost of production, but the lack of ability in technology, the lack of the role of technology, results in the calculation of the cost of production taking quite a long time. The calculation of the cost of production at the Company still uses a manual system so that the company has difficulty calculating the cost of production on a regular basis. The results of this report are designed by the authors to calculate the cost of goods manufacture and the application that can be followed by users at CV Aulia Printing. The author provides suggestions so that companies can apply accounting information systems for cost of goods manufacture that have been designed. Keywords: Accounting Information System, Cost of Goods Manufacture.